2012
DOI: 10.1002/prot.24133
|View full text |Cite
|
Sign up to set email alerts
|

Design of human granzyme B variants resistant to serpin B9

Abstract: Human granzyme B (hGB) is a serine protease involved in immune-mediated apoptosis. Its cytotoxicity makes it potentially applicable in cancer therapy. However, the effectiveness of hGB can be hampered by the cytosolic expression of a natural protein inhibitor, human Serpin B9 (hSB9). Here, we used computational approaches to identify hGB mutations that can affect its binding to hSB9 without significantly decreasing its catalytic efficiency. Alanine-scanning calculations allowed us to identify residues of hGB i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 51 publications
0
29
0
1
Order By: Relevance
“…Gb was produced in HEK293 cells with an N-terminal protective peptide fused to an enterokinase cleavage site (EGb) to suppress the enzymatic activity in the host cells, as previously described (11). Activity was restored by the enzymatic removal of this peptide using 0.02 U of recombinant enterokinase (Novagen; Merck) per g of protein (12). The restored enzymatic activity was confirmed using a colorimetric activity assay (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gb was produced in HEK293 cells with an N-terminal protective peptide fused to an enterokinase cleavage site (EGb) to suppress the enzymatic activity in the host cells, as previously described (11). Activity was restored by the enzymatic removal of this peptide using 0.02 U of recombinant enterokinase (Novagen; Merck) per g of protein (12). The restored enzymatic activity was confirmed using a colorimetric activity assay (13).…”
mentioning
confidence: 99%
“…Reimann, R. Fischer, S. Barth, and R. Fendel, unpublished data), by splicing by overlap extension (SOE)-PCR using a glycine-serine linker peptide and fusing it to the SerpinB9-resistant EGb R201K mutant (12). This was expressed in HEK293-6E cells using a vector based on pTT5 (25) modified with an expression cassette designed for EGb-scFv fusion proteins (26,27).…”
mentioning
confidence: 99%
“…[27][28][29][30] We have addressed this challenge by developing a PI9-independent variant of granzyme B. 31 We previously showed that human granzyme B fused to the humanized single chain antibody H22 (which binds specifically and with high affinity to CD64) induces apoptosis in AML cells.…”
mentioning
confidence: 99%
“…Based on in silico analysis carried out by the German Research School for Simulation Sciences in Jülich, we recently identified the molecular contacts between granzyme B and PI-9 by molecular modeling [144]. The inhibition of granzyme B by PI-9 involves the generation of a reversible Michaelis complex followed by a covalent stoichiometric 1:1 interaction, resulting in the irreversible inactivation of both the enzyme and the inhibitor [81,145,146].…”
Section: Design Of Granzyme B Variants That Are Insensitive Towards Pi-9mentioning
confidence: 99%